PERLINDUNGAN KONSUMEN OLEH PT. XXX TERHADAP PENUMPANG BUS (STUDI KASUS PT. XXX DI KOTA PADANG PANJANG) - Endira, Armaida; Marwenny, Elwidarifa; Citra, Helfira (Ensiklopedia of Journal, 2023)
One of the forms of transportation often used by the people of West Sumatra (Sumbar) is the PT Bus. XXX, Based on LLAJ Law Number 22 of 2009 and PK Law Number 8 of 1999, currently public transport very often provides minimal services to passengers or takes actions that are considered to cause losses to passengers, both materially and non-materially, Sometimes it can even endanger the lives of consumers. Organizing public bus passenger transportation should provide a sense of security, safety and order, all of which are important parts and are one of the main objectives in organizing transportation. The method used in the research is the research approach that the author uses in this research is sociological juridical. And the type of research used is qualitative-descriptive because it is more appropriate to explain PT.XXX's responsibilities. The conclusion that the author got from this research is the responsibility of PT. XXX regarding accident passengers and passenger comfort has not been fully implemented by PT. XXX. The responsibility given is not only insurance but also justice felt by passengers, which is the most important thing passengers need, namely a sense of security, safety and comfort, especially since this is public transportation used by many people.